An Explanatory Sequential Study on Adverse Childhood Experiences and Parental Readiness of Fur Parents - Christian Bandola; Rosie Mae B. De Vera (Research Synergy Foundation Press, 2025)
This study investigated the relationship between Adverse Childhood Experiences (ACEs) and parental readiness among fur parents—individuals who consider their pets children, form deep emotional bonds, and assume caregiving roles akin to traditional parenting. An explanatory sequential design was employed, combining quantitative data with qualitative insights. Participants were adults aged 18 or older who identified as fur parents and had chosen not to have biological children. The ACE-Q and READI-SF instruments were utilized to assess ACE exposure and parental readiness. The READI-SF is a 17-item measure assessing readiness to engage in parenting roles, with higher scores indicating greater readiness. An a priori power analysis suggested a sample size of 115 participants; however, due to the group's niche nature, 81 participants were recruited. Quantitative analysis revealed a weak positive correlation between ACE scores and parental readiness (r = 0.17), which was not statistically significant (p = 0.14). The average ACE score was 0.36 (SD = 0.34), indicating low exposure to adverse experiences, while the average READI-SF score was 3.87 (SD = 0.42), reflecting a moderate level of parental readiness. These findings suggest that, within this sample, a history of adverse childhood experiences does not significantly impact an individual's readiness to assume parenting roles. This may be attributed to the limited sample size or conceptual differences between ACEs and readiness for parental involvement. In the qualitative phase, four key themes emerged: (1) Parental Priorities, revealing factors influencing the choice of fur parenting over biological children; (2) Parental Perspectives, reflecting how past experiences shaped views on parenting; (3) Parental Alternatives, examining outcomes and experiences associated with fur parenting as an alternative to traditional parenting; and (4) Fur Parenting Attachment, illustrating how childhood experiences motivated participants to become better caregivers, not only to their pets but also, potentially, to children in the future. These themes provide context for understanding how fur parents perceive their roles and readiness. Overall, the study underscores the need for further research to identify other potential influences on parental readiness.